2014
DOI: 10.1111/cge.12463
|View full text |Cite
|
Sign up to set email alerts
|

CHIPS for genetic testing to improve a regional clinical genetic service

Abstract: In current practice of clinical genetics, molecular diagnosis has become more widely used than ever before. DNA diagnosis is important for appropriate medical care of the patient, and proper genetic counseling to the family. However, genetic testing of orphan disease cannot always be performed easily. In multiple congenital anomalies (MCA) syndromes by monogenic cause, the broad mutational spectrum and large size of responsible genes often make molecular diagnosis expensive and cumbersome. We solve this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The gene mutations were screened by CHIPS (CEL nuclease mediated heteroduplex incision with polyacrylamide gel electrophoresis and silver staining) technology [Niida et al, 2012a[Niida et al, , 2015 and confirmed by direct sequencing with an ABI 3130xl Genetic Analyser and BigDye version 3.1 Cycle Sequencing Kit (Thermo Fisher Scientific). For patient 3, the SNRPN methylation test was performed according to an established protocol [Kosaki et al, 1997] with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The gene mutations were screened by CHIPS (CEL nuclease mediated heteroduplex incision with polyacrylamide gel electrophoresis and silver staining) technology [Niida et al, 2012a[Niida et al, , 2015 and confirmed by direct sequencing with an ABI 3130xl Genetic Analyser and BigDye version 3.1 Cycle Sequencing Kit (Thermo Fisher Scientific). For patient 3, the SNRPN methylation test was performed according to an established protocol [Kosaki et al, 1997] with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…To solve this problem, over the past few years we have developed a conventional, highly sensitive and inexpensive mutation screening system for large genes. This new technology, CHIPS (CEL nuclease mediated heteroduplex incision with polyacrylamide gel electrophoresis and silver staining) [16,17], has already been successfully applied to our daily clinical genetic service [18]. The aim of this study is to establish a practicable and inexpensive NF1 mutation screening system based on CHIPS technology through the pilot analysis of eight patients with NF1 from five independent families, and prepare for a mutational cohort study of Japan and of molecular pathology of NF1 lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Actually 100% sensitivity of mutation detection has been accomplished using only commercially available reagents and basic apparatus [4,5]. At the same time, CHIPS offers inexpensive easy mutation screening by cutting out the cost and effort of unnecessary sequencing [6]. Here we demonstrate an example of mutation screening of a patient with NF1.…”
Section: Introductionmentioning
confidence: 99%